An Instrument for Assessing Power Distance in Agile Organizations - Preliminary Results - Mattos, Claudio Saraiva; Dutra, Eliezer; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Background: Power Distance is defined as the degree of acceptance in relation to inequality of power among people. In agile organizations, high distance power can lead to restricted communication, reduced collaboration, and resistance to change, which can negatively affect the software quality. However, identifying latent behaviors associated with high power distance is not always straightforward. Objective: We present IDPD, an instrument to assess power distance in agile organizations whose measurement items are based on manifestations of power distance associated with human factors, organizational culture elements, and process-related elements. Method: We followed guidelines for developing psychometric scales. The IDPD was evaluated by an expert judge panel and in a case study in two agile teams. Results: The items were deemed easy to understand, relevant and adequate to evaluate power distance in agile settings. In general, the diagnosis provided in the case study showed little to no effect associated with high power distance on organizational culture elements and human factors. Conversely, high power distance may be impacting process execution and improvement. Conclusion: Initial evidence suggests that the IDPD supports the assessment of power distance in agile teams and provides insights for mitigating its impacts.